Young customers' intention to purchase organic food in South Arica: extending the theory of planned behaviour - Marokhu, Monnye Koketso (My University, 2022)
Ethical consumption has become an increasing trend as young customers are getting increasingly aware of their environmental and ethical responsibilities. The aim of the study was to examine the determinants of organic food purchase intention and behavior of young customers by extending the Theory of Planned Behavior (TPB). The study had the following objectives (1) to determine the effects of TPB constructs (attitude, subjective norms, and perceived behavioral control) on young consumers’ intention to purchase organic food. (2) to investigate whether the extended TPB model would improve the predictive validity of the model. The TPB was modified by the addition of three value constructs (health, environmental and appearance consciousness) as antecedents of attitude and intention and two personal factors (moral norms and ethical self-identity) as predictors of purchase intention. (3) to investigate if attitude towards organic food will mediate the relationship between health, appearance and environmental consciousness and purchase intention (4) to determine the effect of intention on actual purchasing behavior of young consumers and (5) to develop and test a unique multi-dimensional model of young consumers’ intention to purchase organic food. The study adopted a quantitative research approach and data was collected through the cross sectional survey method using self-administered questionnaires. The questionnaires were distributed to the respondents through mall intercept and the Partial Least Square Structural Equation Modelling (PLS SEM) was used to test the hypotheses of the study. The findings confirmed that two constructs of the TPB (attitude towards a behaviour and perceived behavioural control) are predictors of purchase intention. In addition, health and environmental conciousness are antecedents of attitude and intention. Attitude mediates the relationship between health and environmental conciousness and intention. Furthermore, intention is a predictor of behaviour. Recommendations to improve the purchase of organic food focus on communication by marketers to consumers about the benefits of organic food. The limitations and areas for further studies are suggested.
Thesis (M. COM. ( Business Management )) -- University of Limpopo, 2022
Keywords: Theory of Planned Behaviour; Moral norm; Ethical self-identity; Health consciousness; Environmental consciousness; Appearance consciousness; Young customers; Consumer confidence; Consumer satisfaction; Consumer behavior; Consumers -- Attitudes; Self-consciousness (Awareness); Ethics; Natural foods